Blockade of CXCR1/2 chemokine receptors protects against brain damage in ischemic stroke in mice - Larissa Fonseca da Cunha Sousa; Fernanda Matos Coelho; David Henrique Rodrigues; Alline Cristina Campos; Luciola da Silva Barcelos; Mauro Martins Teixeira; Milene Alvarenga Rachid; Antonio Lucio Teixeira (Clinics, 2013)
OBJECTIVE: Ischemic stroke may result from transient or permanent reductions of regional cerebral blood flow. Polymorphonuclear neutrophils have been described as the earliest inflammatory cells to arrive in ischemic tissue. CXCR1/2 receptors are involved in the recruitment of these cells. However, the contribution of these chemokine receptors during transient brain ischemia in mice remains poorly understood. In this work, we investigated the effects of reparixin, an allosteric antagonist of CXCR1/2 receptors, in a model of middle cerebral artery occlusion and reperfusion in mice. METHODS: C57BL/6J male mice treated with reparixin or vehicle were subjected to a middle cerebral artery occlusion procedure 1 h after the treatment. Ninety minutes after ischemia induction, the monofilament that prevented blood flow was removed. Twenty-four hours after the reperfusion procedure, behavioral changes, including motor signs, were analyzed with the SmithKline/Harwell/lmperial College/Royal Hospital/Phenotype Assessment (SHIRPA) battery. The animals were sacrificed, and brain tissue was removed for histological and biochemical analyses. Histological sections were stained with hematoxylin and eosin, neutrophil infiltration was estimated by myeloperoxidase activity and the inflammatory cytokine IL-iβ was measured by ELISA. RESULTS: Pre-treatment with reparixin reduced the motor deficits observed in this model of ischemia and reperfusion. Myeloperoxidase activity and IL-iβ were reduced in the reparixin-treated group. Histological analysis revealed that ischemic injury was also attenuated by reparixin pre-treatment. CONCLUSIONS: Our results suggest that the blockade of the CXCR1/2 receptors by reparixin promotes neuroprotective effects by reducing the levels of polymorphonuclear infiltration in the brain and the tissue damage associated with middle cerebral artery occlusion and reperfusion.